2019
DOI: 10.3390/ani9100792
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxytocin in the Dog–Owner Relationship

Abstract: Simple SummaryA number of studies have shown that when dogs and humans interact with each other in a positive way (for example cuddling) both partners exhibit a surge in oxytocin, a hormone which has been linked to positive emotional states. It is not clear however, if this increase in oxytocin occurs between any dog and human or whether this is more specific to the dog–owner bond. In this study we measured oxytocin levels in dogs and humans before and after they interacted with their closely bonded partner (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 73 publications
(128 reference statements)
0
32
0
Order By: Relevance
“…Other studies have found that dogs' variation in their oxytocin receptor gene is related to certain breeds of dogs' social behavior when greeting unfamiliar people ( 77 , 78 ) as well as dogs' attachment behaviors directed to their owners ( 50 ). As the oxytocin pathway has been discussed as a potential mechanism underlying positive human-dog interactions ( 79 , 80 ), these individual differences across dogs may be important for understanding variability across studies.…”
Section: Variability In Animal Participants In Hai Researchmentioning
confidence: 99%
“…Other studies have found that dogs' variation in their oxytocin receptor gene is related to certain breeds of dogs' social behavior when greeting unfamiliar people ( 77 , 78 ) as well as dogs' attachment behaviors directed to their owners ( 50 ). As the oxytocin pathway has been discussed as a potential mechanism underlying positive human-dog interactions ( 79 , 80 ), these individual differences across dogs may be important for understanding variability across studies.…”
Section: Variability In Animal Participants In Hai Researchmentioning
confidence: 99%
“…Oxytocin not only buffers the stress response and cortisol secretion ( 68 ) but is also involved emotion, trust, and bonding ( 69 ). The oxytocin system has been hypothesized to be a primary mechanistic pathway involved in human-dog interactions ( 70 ). Positive dog-owner interactions including stroking, petting, and talking have been shown to result in increased oxytocin levels in both dog owners and dogs, which has been related to the strength of the owner-dog relationship ( 71 ) and dog-human affiliative behaviors ( 72 , 73 ).…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
“…In dogs, OXT has become a biomarker commonly investigated in behavioral and neuroendocrinological research, but, in contrast to the investigation on serotoninergic system, commonly associated with aggressive behavior [19], the oxytocinergic system has been frequently linked to sociopositive human-dog interaction [20]. Actually, the behavioral effects of oxytocin in dogs are mainly based on three macro-areas: the effect of human-dog social interaction on peripheral oxytocin levels, the associations between the polymorphisms in oxytocin receptor gene and social behavior, and the effect of exogenous oxytocin administration on dogs' social behavior [21].…”
Section: Introductionmentioning
confidence: 99%